FAKTOR DETERMINAN KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA BAUBAU - Hasan, Waode Adriani; Musrifa, Yuli (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine whether taxpayer awareness, tax knowledge, tax sanctions and public service accountability affect the compliance of motor vehicle taxpayers in Baubau City. The data was collected using a questionnaire distributed to 100 sample respondents selected using the slovin formula. The data analysis method used is multiple linear analyses. The results showed that taxpayer awareness affects motor vehicle taxpayer compliance. Tax knowledge has no effect on motor vehicle taxpayer compliance. In addition, tax sanctions have no effect on motor vehicle taxpayer compliance in Baubau city, and public service accountability has no effect on motor vehicle taxpayer compliance in Baubau city